Strategi Pengembangan Potensi Pariwisata di Pantai Blimbingsari Kabupaten Banyuwangi - Febriani Jayadi, Melly; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 8 No 1 (2020): VOL 8, NO 1 (2020): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATA, 2020)
Banyuwangi Regency is an area that has a variety of tourism potential either natural, cultural and artificial potential. One of the tourist attractions with its natural potential is Blimbingsari Beach. Blimbingsari Beach is one of the tourist attractions located in Banyuwangi Regency which is famous for its distinctive culinary fish. Currently tourists visit Blimbingsari Beach is still small compared to other tourist attractions. Tourism potential in Blimbingsari Beach is able to attract many tourists to visit by developing its tourist potential. This study used primary data sources obtained directly by observation and interviews, and data analysis techniques used in this study is a SWOT analysis which is a qualitative analysis tool that is done by examining internal and external factors. SWOT analysis compares the external factors which are opportunities and threats with internal factors which are strengths and weaknesses. The results of this study shows that the development of Blimbingsari beach tourism potential can still be developed further through existing potential. Blimbingsari beach managers should promote more so that Blimbingsari beach is known to many people. Keyword: Strategy Development, Potential, Beach, Tourism